The Effect of Dietary and Exercise in Obesity and Overweight as Protecting Factor of Osteoarthritis - Hermilasari, Rista Dwi; Harry Allan Papendang (Sean Institute, 2023)
Osteoarthritis (OA) is a major global public health issue. It can be harmed the knee, hands, hip, and spine joints. Overweight and obesity are the main risk factor for osteoarthritis. Weight loss and exercise are needed to reduce the adverse effect of osteoarthritis. This review is purposed to find out if dietary or exercise or both are effective to reduce the symptoms of osteoarthritis. The review uses searching literatures method that has been derived from PubMed database. Inclusion criteria and exclusion criteria were using to filtered the proper articles. The results discovered that weight loss are effective for osteoarthritis patients with higher BMI, it minimises the knee's compressive pressures and prevented the progression of the maximum and mean extrusion lengths. The exercise can help avoid inflammation in OA. For both non weight bearing quadriceps improving exercise and weight bearing functional activity enhanced the results of pain and function over a 12-week period. Some studies suggest that combination of dietary and exercise might help to improve quality of life in OA patients. The Intensive Diet and Exercise for Arthritis (IDEA) lowering knee pain significantly and also improving in clinical results. We concluded that combination of exercise and dietary as recommended non pharmacologic treatment of osteoarthritis. Though in some aspect dietary only may give advantages to OA patients with overweight or obesity.